Intermediation in networks - Jan-Peter Siedlarek (Fondazione Eni Enrico Mattei (FEEM), 2012)
This paper studies bargaining and exchange in a networked market with intermediation. Possibilities to trade are restricted through a network of existing relationships and traders bargain over the division of available gains from trade along different feasible routes. Using a stochastic model of bargaining, I characterize stationary equilibrium payoffs as the fixed point of a set of intuitive value function equations and study efficiency and the relationship between network structure and payoffs. In equilibrium, trade is never unduly delayed but it may take place too early and in states where delay would be efficient. The inefficiency arises from a hold-up threat and the inability of bargaining parties credibly to commit to a split in a future period. The model also shows how with competing trade routes as trade frictions go to zero agents that are not essential to a trade opportunity receive a payoff of zero.
Keywords: C73; C78; L14; 330; Stochastic Games; bargaining; Random Matching; Middlemen; Network